2012
DOI: 10.1177/030089161209800506
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Melanoma: A Regional Review and Future Directions

Abstract: . Our results are comparable to published data. Malignant melanoma is a disease with rising incidence and limited treatment options. These patients are best treated in the context of clinical trials as new targeted therapies are promising as future strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
11
1
1
Order By: Relevance
“…MM accounts for 60-80% of deaths from all skin cancers globally with New Zealand and Australia having the highest incidence [2][3][4]. The 5-year survival of metastatic MM (mMM) is 5-19% depending on the site of the metastasis [2,5] with an overall median survival of 5-9 months [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…MM accounts for 60-80% of deaths from all skin cancers globally with New Zealand and Australia having the highest incidence [2][3][4]. The 5-year survival of metastatic MM (mMM) is 5-19% depending on the site of the metastasis [2,5] with an overall median survival of 5-9 months [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although stage 4 metastatic melanoma is rarely curable, a few new approaches have shown clinical benefit by prolonging overall survival in randomized trials (10). Current treatment regimes of stage 4 melanoma include chemotherapy and immunotherapy (11). One of the most promising treatment options is oral Vemurafenib, a standard treatment for metastatic melanoma (12).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…6,7 Unfortunately, treatment outcomes are not satisfactory and patients' responses to most of these therapies are very poor. 8 At present, the most common drug used for the treatment of melanoma is dacarbazine (DTIC), which is a US Food and Drug Administration (FDA)-approved, first-line treatment for patients with wild-type melanomas. 9 Although in vitro experiments showed that DTIC produced cytotoxicity in many melanoma cell lines, the response to DTIC was only 5%−10% when used alone.…”
Section: Introductionmentioning
confidence: 99%